Did you listen to the beat? Auditory steady-state responses in the human electroencephalogram at 4 and 7 hz modulation rates reflect selective attention - Jaeger, M; Bleichner, MG; Bauer, AKR; Mirkovic, B; Debener, S (Springer US, 2018)
The acoustic envelope of human speech correlates with the syllabic rate (4–8 Hz) and carries important information for intelligibility, which is typically compromised in multi-talker, noisy environments. In order to better understand the dynamics of selective auditory attention to low frequency modulated sound sources, we conducted a two-stream auditory steady-state response (ASSR) selective attention electroencephalogram (EEG) study. The two streams consisted of 4 and 7 Hz amplitude and frequency modulated sounds presented from the left and right side. One of two streams had to be attended while the other had to be ignored. The attended stream always contained a target, allowing for the behavioral confirmation of the attention manipulation. EEG ASSR power analysis revealed a significant increase in 7 Hz power for the attend compared to the ignore conditions. There was no significant difference in 4 Hz power when the 4 Hz stream had to be attended compared to when it had to be ignored. This lack of 4 Hz attention modulation could be explained by a distracting effect of a third frequency at 3 Hz (beat frequency) perceivable when the 4 and 7 Hz streams are presented simultaneously. Taken together our results show that low frequency modulations at syllabic rate are modulated by selective spatial attention. Whether attention effects act as enhancement of the attended stream or suppression of to be ignored stream may depend on how well auditory streams can be segregated.